Multiport Routing of Topologically Optical Transport Based on Merging of Valley-Dependent Edge States and Second-Order Corner States - Li, Meng-Yu; Chen, Wen-Jie; He, Xin-Tao; Dong, Jian-Wen (Frontiers in Physics, 2022)
Topological photonics provide a novel platform to robustly manipulate the flow of light and design high-performance nanophotonic devices. To do this, a fundamental mechanism is the flexible control of optical transport based on topological boundary states on edges or corners. In this work, we design a multiport device to route the topologically optical transport, by using both valley-dependent edge states (VDESs) and second-order corner states (SOCSs). The VDESs are derived from sublattice symmetry breaking in honeycomb lattice, while SOCSs are induced by lattice deformation of Kagome lattice. In terms of unit cell, we find that both two configurations can be reconsidered as a same triangular-lattice photonic crystal, which consists of hexagon-profile air holes array in silicon background. Therefore, a four-port device is designed based on the two configurations. In simulation, we observe the frequency-dependent routing effect of topologically optical transport, by merging of VDESs and SOCSs. This work not only shows a novel platform to explore various topological phases in photonic system, but also provides guidance in the development of topological photonic integrated circuits with mode division multiplexing.